TINJAUAN YURIDIS PENCABUTAN HAK POLITIK DALAM TINDAK PIDANA KORUPSI - Hariansyah Hariansyah (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT This study aims to find out the basis of judges' considerations in imposing additional criminal sanctions in the form of revoking political rights and knowing that the revocation of political rights is forever or only during serving a sentence. This research was carried out at the Samarinda Corruption Court. The results of the study revealed that the number of recent corruption cases (in 2016) amounted to 72. Of these, none of them received additional criminal sanctions in the form of revocation of political rights. This then requires the writer to conduct a normative juridical research method that is by obtaining data and information from the literature review, namely books, documents relating to cases such as indictments, judges' decisions, and legislation against one case of revoking political rights in corruption act precisely the case of Djoko Susilo. The findings obtained in this study are: 1) Application of Revocation The right to vote and be elected in a public office which is contained in the Supreme Court Decision Number 537 / Pid.Sus / 2014 which was handed down to the defendant Djoko Susilo is inappropriate, because it is not in accordance with Article 38 of the Criminal Code . The article states that the length of the revocation of the right to imprisonment or confinement is a two-year minamal and a maximum of five years longer than the principal sentence. Whereas in the Aquo case, the Panel of Judges did not determine the length of revocation of the right to the defendant, which could be interpreted as saying that Djoko Susilo could not use the right for life even though he had finished serving his sentence. 2) Judge's parameter in imposing a verdict in the form of additional criminal acts in the form of revocation of the right to vote and be elected in the public office imposed on the defendant Djoko Susilo is more to the deterrent effect on the perpetrators of corruption and also as a preventive measure to reduce corruption in Indonesia. Keywords: Revocation of Political Rights, Corruption, Basic Judicial Considerations, Length of Revocation